Peran Guru Dalam Meningkatkan Literasi Digital Bagi Siswa Kelas X Di SMA Swasta Adhyaksa - Banda, Yosef Moan; Rima, Putri Yunianti (Ekspektasi: Jurnal Pendidikan Ekonomi, 2023)
This research aims to determine the role of teachers and digital literacy activities for class X students at Adhyaksa Ende Private High School. This type of research is qualitative with a qualitative descriptive approach. The research subjects were teachers and students, with data collection methods: interviews, observation, and documentation. The research results show that the role of class X teachers in digital literacy is that students are allowed to do literacy for 15 minutes. Besides reading books, students can also read digitally using cell phones. The Digital literacy activities make students enthusiastic because they can access what they need to learn and better understand technological developments. Thus, with digital literacy, students, teachers, and education staff feel helped because they can access, understand, and use digital media as a communication tool. It also positively impacts students' learning because, with digital literacy, students can increase their knowledge of technology.